DYNAMICS OF VILLAGE UNIT CO-OPERATIVE DEVELOPMENT (CASE STUDY ON KUD TANI MAKMUR IN KASIHAN DISTRICT) - Abi Pratiwa Siregar; Ahmad Samsudin; Moh Ali Abdulrahman (Universitas Tadulako, 2020)
This study aims to (a) determine the dynamics of the development of KUD Tani Makmur (aspects of the organization, type of business, and finance) and (b) determine the forecasting model to estimate turnover. The basic method used is descriptive-analytical. Meanwhile, the data analysis used is descriptive analysis, financial ratios, and trends (linear, quadratic, and exponential). Based on the results of the study, it is known that KUD Tani Makmur has experienced dynamic developments: (a) the number of members, principal savings, mandatory savings, voluntary savings, and the number of managers grew by 2.59%, 27.83%, 9.36, 29.09%, and 1.51% per year, (b) the number of business units managed from 1994 to 2000 was 12 units, but gradually decreased to 4 business units in 2018, and (c) liquidity grew by around 7.37% (current ratio), 8.22% (quick ratio), and 0.81% (cash ratio) per year. Solvability is 2.92% lower, while the debt to equity ratio is 5.06% per year. Meanwhile, profitability consisting of profit margin, return on equity, and return on total assets grew by 0.17%, 0.30%, and 0.08% per year. Finally, the quadratic method is the best with the equation Ŷ = 1.132.252.474 + 1.345 .500X + 10,629,725 X2. The proposed policy implications are (a) Validation of membership to find out the real number of active and passive members, (b) Running a regeneration program to prepare management and supervisors in the future, (c) Organizing education and training on information technology to improve knowledge and ability of HR, (d) Increase own capital through optimization of compulsory savings payments and transaction activities of members, and (e) Further research needs to be done to compare various forecasting methods by separating short-term, medium-term and long-term forecasting.